SMAC mimetics sensitize HIV-infected cells to oncolytic virus-mediated death - Molyer, Bengisu; Ameeriar, Yasmeen; Angel, Jonathan B. (Frontiers in Immunology, 2025)
Elimination of latently and persistently HIV-infected cells is one of the main barriers to finding a cure for HIV. We have demonstrated that cells latently/persistently infected with HIV impair interferon signaling, which makes them susceptible to selective infection and killing by the oncolytic virus (OV) MG1. Sensitizing these cells to MG1-mediated killing can be expected to make MG1 a more effective therapeutic. As small-molecule second mitochondria-derived activator of caspases (SMAC) mimetics have been shown to increase OV-mediated death in cancer models, we used the SMAC mimetics LCL-161 and birinapant alongside MG1 to enhance the killing of HIV-infected cell lines and monocyte-derived macrophages (MDMs). We show that SMAC mimetics enhance MG1-mediated death, but that this is not a result of an increase in OV infection. This cell death occurs via both caspase-dependent and caspase-independent mechanisms and is not completely dependent on tumor necrosis factor alpha (TNFα). Together, these results show that the use of SMAC mimetics alongside OVs may be a viable strategy to eradicate latently/persistently HIV-infected cells.